2016
DOI: 10.1152/physrev.00024.2015
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to Clinical Cancer Therapy: A Twist in Physiological Signaling

Abstract: Although modern therapeutic strategies have brought significant progress to cancer care in the last 30 years, drug resistance to targeted monotherapies has emerged as a major challenge. Aberrant regulation of multiple physiological signaling pathways indispensable for developmental and metabolic homeostasis, such as hyperactivation of pro-survival signaling axes, loss of suppressive regulations, and impaired functionalities of the immune system, have been extensively investigated aiming to understand the diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 338 publications
(229 reference statements)
1
42
0
Order By: Relevance
“…These orchestrated signaling networks contribute to meet the increased metabolic demand of cancer cells, to promote uncontrolled proliferation and survival, and stimulate migration/invasion. Consistent with the cellular functions regulated by PKB, its hyperactivation is observed predominantly in poorly differentiated tumors that are invasive, fast growing, and resistant to treatment and correlated clinically with poorer outcomes [30].…”
Section: Pkb Activation Drives Cancer Developmentmentioning
confidence: 74%
“…These orchestrated signaling networks contribute to meet the increased metabolic demand of cancer cells, to promote uncontrolled proliferation and survival, and stimulate migration/invasion. Consistent with the cellular functions regulated by PKB, its hyperactivation is observed predominantly in poorly differentiated tumors that are invasive, fast growing, and resistant to treatment and correlated clinically with poorer outcomes [30].…”
Section: Pkb Activation Drives Cancer Developmentmentioning
confidence: 74%
“…The upstream triggers include activating mutations on NRAS, as well as amplification or alternative splicing of the mutated BRAF gene. Downstream reactivation of the MAPK pathway through activating mutations on MEK proteins has also been documented 91 . Re-dimerization of the kinase-dead form of mutant BRAF with endogenous CRAF, unfavourable disruption of the ERKdependent negative feedback signaling loop, upregulation of other pro-oncogenic molecules, such as RTKs , RTK ligands like HGF and COT have also been described 91 .…”
Section: Wnt Signalling and Brafi Resistance: Minos The Minotaur Thmentioning
confidence: 99%
“…Downstream reactivation of the MAPK pathway through activating mutations on MEK proteins has also been documented 91 . Re-dimerization of the kinase-dead form of mutant BRAF with endogenous CRAF, unfavourable disruption of the ERKdependent negative feedback signaling loop, upregulation of other pro-oncogenic molecules, such as RTKs , RTK ligands like HGF and COT have also been described 91 . All of these mechanisms ultimately trigger the reactivation of MAPK and PI3K/Akt signaling that, in turn, drive melanoma cell survival.…”
Section: Wnt Signalling and Brafi Resistance: Minos The Minotaur Thmentioning
confidence: 99%
“…The emergence of drug resistance mainly arises from the overexpression of membrane proteins that activate the efflux pump, thereby exporting drugs before they reach their intracellular sites of action. [3][4][5] Pgp, a typical drug-efflux transporter, has received increasing attention, Accordingly, considerable efforts have been focused on inhibiting the function of Pgp and ultimately increasing intracellular accumulation of drugs. 7 Previous studies have reported various inhibitors that were designed to block Pgp activity.…”
Section: Introductionmentioning
confidence: 99%